The effect of physical activity, nutritional status and learning motivation on the physical fitness of public elementary school students 02 Senamat Bungo Regency - Muhammad Afdhori; Damrah Damrah; Willadi Rasyid; Hendri Neldi (Jorpres (Jurnal Olahraga Prestasi), 2023)
The purpose of this study was to determine the effect of physical activity, nutritional status and learning motivation on students' physical fitness. This type of quantitative research, with the research design carried out with a Path Analysis approach. The sample in this study amounted to 50 students, data was collected using the PAQ-C questionnaire to measure students' physical activity, and using the Nusantara Student Physical Fitness Test (TKPN) to measure students' nutritional status and physical fitness, while to measure learning motivation using questionnaires. Research Results (1). that physical activity on physical fitness is 30.91%. (2). The effect of nutritional status on physical fitness is 12.25%. (3). The effect of learning motivation on physical fitness is 5.56%. (4). The effect of physical activity through learning motivation on physical fitness is 11.25%. (5). The effect of nutritional status through learning motivation on physical fitness is 8.89%. This means that hypotheses related to the indirect influence of nutritional status through learning motivation on physical fitness are acceptable. (6). Physical activity, nutritional status and learning motivation affect physical fitness. The similarity of pathways from various physical activity, nutritional status, and learning motivation to affect physical fitness (X1, X2 and X3 to Y) is 92%. This figure shows that the magnitude of the influence of physical activity variables, nutritional status and learning motivation has a significant effect on physical fitness. Physical activity, nutritional status, and learning motivation had a significant influence on students' physical fitness, and the complex interactions between the three had a strong impact in the context of this study